Hubungan Tajam Penglihatan pada Penderita Hipertensi yang Mengalami Obesitas: (Literature Review) - Nur Halifa Maharani Hairuddin; Andi Kartini Eka Yanti; Purnamanita Syawal (Pusat riset dan Inovasi Nasional, 2026)
Hypertension, a global health issue, is increasingly prevalent and significantly contributes to morbidity and mortality. It often coexists with obesity, a key risk factor for hypertension and vascular complications. The combination of hypertension and obesity leads to metabolic changes, chronic inflammation, and oxidative stress that damage retinal blood vessels, directly affecting visual acuity. This literature review examines the relationship between hypertension, obesity, and visual acuity, analyzing 20 articles published between 2021 and 2025, sourced from PubMed, Google Scholar, and ScienceDirect. The study found a significant association between hypertension and obesity with decreased visual acuity. Obesity not only serves as a comorbidity but also as a mediator, worsening hypertension's effects through mechanisms like insulin resistance and endothelial dysfunction. Longitudinal studies indicate that visual impairment is progressive, while cross-sectional studies highlight its high prevalence in hypertensive obese populations. The review emphasizes the need for routine eye exams, blood pressure control, and weight management as preventive measures. In conclusion, hypertension and obesity together significantly increase the risk of visual impairment, necessitating a multidisciplinary approach to care and promoting preventive strategies to preserve eye health and enhance patients' quality of life.